Effect of Acupuncture on ST36 Acite Stitches to Accessible Epitelization Accuracies in Rats of Rats Infected of MRSA Bacteria - Sayogo, William (Journal of Global Research in Public Health, 2018)
Background: Epithelialization is part of skin tissue regeneration to repair the damage . This process will be inhibited by the presence of bacterial infections, especially Methicillin resistant Staphylococcus aureus (MRSA ) . Methods: This study aims to determine the effect of stabbing acupuncture needles on ST36 acupoint on epithelization on the healing process of MRSA infected wounds in the skin of wisting rats . Thirty six Wistar rats , 3 months old , are divided into 6 groups , 2 groups of negative control , 2 groups of positive control , 2 groups of treatment group (All are sacrificed on the fourth day and sixth day ) . Injury to the back skin of rats with a knife along the incised 2 cm and depth to subcutaneous . Wound of positive control groups infected by MRSA , wound in the treatment groups also infected MRSA and stabbing at ST36 acupoints . Each group are sacrificed to / for day 4 and 6 , the skin tissue is fixed , made histological preparations , stained with HE . Results: The measurement of the epithelial length using Optilab mounted on a light microscope . The data are analyzed by comparing the mean and SD . The epithelial length of the treatment group is higher than the positive control (0,46±0,19 ) vs (0,21±0,16 );(0,63±0,76 ) vs (0,42±0,301 ) , being compared with the negative control is not much different . Conclusion: Stabbing acupuncture needles on ST36 acupoint accelerates epithelialization in wound healing of the skin MRSA-infected rat.